Dynamic Frequency Regulation Method Based On Thermostatically Controlled Appliances in the Power System. (June 2016) - Rui, Xinyang; Liu, Xingwei; Meng, Jian
Abstract: This paper presents a dynamic frequency regulation strategy which uses residential thermostatically controlled appliances (TCA) to alleviate frequency deviations caused by high penetration of renewable energy sources in the power system. Heating, ventilating and air-conditioning (HVAC) load is used as an example of TCA load. With the control strategy, HVAC units respectively collect frequency information locally, based on which their on/off status is dynamically regulated. The simulation is implemented with 1000 HVAC units in a British Grid model. The results demonstrate that the strategy effectively alleviate the frequency deviations caused by renewable energy sources. A frequency response ability assessment method based on a dynamic load-sorting strategy is also presented.